Characterization of SNEDDS Formulated with Single Bulb Garlic and its Anti-Inflammatory Effect on 3T3-L1 - Lestari, Sri Rahayu; Sunaryono, Sunaryono; Susanto, Hendra; Rachmawati , Hidajah; Irawanto, Rony; Miasih, Dewi Sekar; El Baroroh, Alif Rosyidah; Annisa, Yuslinda; Djati, Muhammad Sasmito (Bogor Agricultural University, Indonesia, 2025)
Inflammation is an early symptom of a disease that reduces the level of health. Single-bulb garlic (Allium sativum L.) is used medicinally as a plant with a broad pharmacological effect, especially anti-inflammatory activity. Self-nanoemulsifying drug delivery systems (SNEDDS) have offered opportunities to improve drug delivery. The current study aimed to characterize SNEDDS-single bulb garlic extract (SBGE) and determine its potential as an anti-inflammatory agent in 3T3-L1 cells. SNEDDS was formulated from tween-80, glycerol, canola oil, and SBGE. The formula characterization is done using droplet size, polydispersity index, zeta potential, physical stability test, and antioxidant assay. The cytotoxicity test of SNEDDS-SBGE was evaluated using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The anti-inflammatory activity was examined using 3T3-L1 cell methylglyoxal (MG) induction, and the expression of cytokines was measured using immunocytochemistry (ICC). The SNEDDS-SBGE had a nanoemulsion size of 42.30±1.39 nm, 0.6±0.03 for the polydispersion index, and -22.63±0.75 mV for the zeta potential. SNEDDS-SBGE was physically stable and had a high antioxidant level (47.579±8.017 %). SNEDDS-SBGE exhibited no toxic effect on 3T3-L1 cells. The administration of 62.5 µg/ml and 125 µg/ml SNEDDS-SBGE could inhibit (p<0.05) the expression of IL-1β after methylglyoxal induction. Thus, SNEDDS-SBGE may have potential anti-inflammatory properties.